2017
DOI: 10.3329/bmrcb.v42i1.31997
|View full text |Cite
|
Sign up to set email alerts
|

Follicular Variant of Papillary Thyroid Carcinoma on the Basis of His-topathological and Immunohistochemical Diagnosis

Abstract: A significant increase in incidence of papillary thyroid carcinoma (PTC) has been noticed in recent decades worldwide. This is due to advances in medical surveillance, increased use of ancillary tests, and a minor component due to over diagnosis of PTC. Follicular variant of papillary thyroid carcinoma (FVPTC) is the second most common variant of PTC and comprises about 23-41%. It is difficult to diagnose histologically when the distinctive nuclear features are either not well developed or present focally with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…The sensitivity of CK19 expression in diagnosis of Papillary carcinoma as recorded by previous researchers ranged from70% to 85% [22][23][24]. The present study reported a higher sensitivity reaching 87.5% encouraging the use of Ck19 taking into account the intensity and distribution of expression in the tumor.…”
Section: Cd117 Expression (Dab Immunoperoxidase) (A) Negativity Withsupporting
confidence: 54%
“…The sensitivity of CK19 expression in diagnosis of Papillary carcinoma as recorded by previous researchers ranged from70% to 85% [22][23][24]. The present study reported a higher sensitivity reaching 87.5% encouraging the use of Ck19 taking into account the intensity and distribution of expression in the tumor.…”
Section: Cd117 Expression (Dab Immunoperoxidase) (A) Negativity Withsupporting
confidence: 54%